Evaluating employee attitudes on working home style during Covid-19 pandemic - Yener, Huseyin (Technium Social Sciences Journal, 2022)
Working life has been experiencing a new break with the Covid-19 making working home model as a new normal. In this study, a model was developed and observed changing attitude of employees about working home model. A questionnaire applied to 405 participants from different job sectors and positions. According to the results of the study, employees continue to support working home arrangements with a declining tendency (from 60s % to 50s %) and they do not want to turn back to office work completely nor continue to work from home every day. Majority wants to continue 1-2 days in a week working home arrangements in the future. Employees do not feel themselves productive in working home arrangements however they worked more hours than office work and they feel isolated and unproductive. It is recommended that organizations apply a hybrid type of working model according to organizational needs and employee opinions